PENGARUH MOTIVASI, KOMPENSASI DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA GURU SMK KABUPATEN BIREUEN - Fadhli, Fadhli; Marwan, Marwan (LPPM-UNIKI, 2020)
The purpose of this study was to determine a) The effect of teacher's motivation to affect Job Satisfaction in Teachers in Vocational Schools in Bireuen Regency, b). Influence of Compensation on Job Satisfaction in Teachers in Vocational Schools in Bireuen District, c). The climate of the School organization on Job Satisfaction in Teachers in Vocational Schools in Bireuen District, and d). The effect of Work Motivation, Compensation, and Organizational Climate simultaneously on Job Satisfaction in Teachers in Vocational Schools in Bireuen District. This type of explanatory research that explains the causal relationship and influence between variables through hypothesis testing, so that the influence of independent variables is known namely work motivation (X1), Compensation (X2), Organizational Climate (X3) on dependent variables, namely Teacher Job Satisfaction (Y). The research method is quantitative, with a path analysis approach to the research sample of 184 teachers in vocational schools in Bireuen Regency in 2020. The results of the analysis, indicate the influence of teacher motivation on vocational teacher satisfaction by 7.34%. The influence of the Compensation factor on Vocati-onal Teacher Satisfaction is 13.33%. And there is the influence of the climate of school organizations on vocational teacher satisfaction by 55.00%. Descriptive analysis results, found that, a). the level of teacher motivation is good, reaching 82.55%. b). Expected Compensation Level has reached 82.36%, and c). School climate support for teacher satisfaction reaches 87.56%. As well as d). The level of teacher satisfaction reached the good category, which was .83.57%, than expected. Based on the coefficient of determination statistics explained that the contribution of work motivation, organizational compensation and climate factors to the satisfaction of state Vocational School teachers in Bireuen was 76.1%.